The Contribution Of Community Learning Centers (PKBM) To Cultivating English Language Interest Among Non-Formal Learners - Sudirman, Sudirman (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the role of the Lentera Nusa Cendikia Community Learning Center (PKBM), located in Kamasan, Monjok Village, Selaparang Sub-district, Mataram City, in The Contribution of Community Learning Centers (PKBM) to Cultivating English Language Interest Among Non-Formal Learners. Using a qualitative approach with a case study design, data was collected through in-depth interviews, observations, and questionnaires of 15 students and teachers. The results showed that PKBM plays an important role in increasing students' confidence and motivation through contextualized learning and integration of technology such as learning apps and videos. As many as 80% of students reported an increase in self-confidence, and 90% expressed high motivation to learn English after attending the program at PKBM. However, limited facilities and access to technology remain a major challenge. This study recommends improving infrastructure and training teachers to maximize the potential of technology-based learning in non-formal environments.